PEMBUATAN PERMEN JELLY EKTRAK JAHE MERAH DENGAN PENAMBAHAN KARAGENAN - Bactiar, Alridho; Ali, Akhyar; Rossi, Evy (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research is to get the precise formulation of the red ginger extract and carrageenan thus producing jellycandies with good quality and appropriate quality standard based on SNI 3574-2-2008 jelly candies. This study was conducted experimentally using a completely randomized design (CRD) with five treatments and three replications. The treatment in this study was JK1 = red ginger extract + carrageenan (41.50 + 7.50), JK2 = red ginger extract + carrageenan (40.50 + 8.50), JK3 = red ginger extract + carrageenan (39.50 + 9.50), JK4 = red ginger extract + carrageenan (38.50 + 10.50), and JK5 = red ginger extract + carrageenan (37.50 + 11.50). Data were analyzed using analysis of variance and in a further test using DNMRT at 5% level. The treatment provides significant effect on moisture content, ash content, acidity (pH), reducing sugar, antioxidant and colour, aroma, taste descriptively. The best treatment in this study was JK1 = red ginger extract + carrageenan (41.50 + 7.50), with a water content of 12.84%, ash content of 0.85%, the degree of acidity (pH) 6.47, reducing sugar 19.74% and antioxidant 2.77 µg/ml as well as having the characteristics of 3.13 (slightly yellow-brown colour), 2.10 (ginger-flavored red), 2.23 (spicy flavor) and 3.20 (slightly chewy texture) and an overall assessment of jelly candy ginger extract and preferably carrageenan by panelist’s. Keywords :Jelly, red ginger and carrageenan.